Studi Evaluasi dan Perencanaan Sistem Drainase Perkotaan di Kecamatan Garum Kabupaten Blitar Provinsi Jawa Timur - Gunawan, Rachmat Ady; Sholichin, Moch; Chandrasasi, Dian (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Garum District, especially in Slorok Village, is a densely populated residential area that has under gone many land use changes. The condition of the land as a green open space has changed its function into a residential and office area. One of the impacts is disasters on direct surface runoff and a decrease in the quantity of water that infiltrates the ground, resulting in flooding during the rainy season, so the need for handling, among others, is rehabilitation of drainage channels and planning of infiltration wells. The calculation results show that there are 37 drainage channels, but there are 7 channels that cannot reduce runoff due to land use changes and the existing drainage cannot be filled. The calculation of the rehabilitation of the dimensions of the canal and the dimensions of the infiltration well is invincible with the existing land, then the dimensions of the infiltration well will be divided by the runoff discharge to see how many wells to be built. The calculation of infiltration wells uses the Sunjoto formula. With the results of the calculation of the dimensions of the infiltration well for a diameter of 1.2 m and a well depth of 2.4 m.